If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 5x + -54 = 72 + -6x Reorder the terms: -54 + 7x + 5x = 72 + -6x Combine like terms: 7x + 5x = 12x -54 + 12x = 72 + -6x Solving -54 + 12x = 72 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -54 + 12x + 6x = 72 + -6x + 6x Combine like terms: 12x + 6x = 18x -54 + 18x = 72 + -6x + 6x Combine like terms: -6x + 6x = 0 -54 + 18x = 72 + 0 -54 + 18x = 72 Add '54' to each side of the equation. -54 + 54 + 18x = 72 + 54 Combine like terms: -54 + 54 = 0 0 + 18x = 72 + 54 18x = 72 + 54 Combine like terms: 72 + 54 = 126 18x = 126 Divide each side by '18'. x = 7 Simplifying x = 7
| 2c-58=7c-24 | | -15=5b+12-2b+b | | 3x+2+2x-1=6x-20 | | 35.8x+5.90=220.7 | | 17=6z-1 | | 36+(4x-9)=c(2x+1)+25 | | .666=3r | | 18x^2+18y^2-12x+9y+7=0 | | x^2-15x-15=-6x-5 | | -5+-16= | | 2b-8=0.4 | | (4x+7y)+(x-3y)= | | 5-2x=-5-x | | k+(4.21)=19.3 | | 13x+50=180 | | x^2-13x+28=-2x+4 | | -8=6b-14 | | 66.6=3r | | 3e=.75 | | x^2+13x+41=5 | | -(8y+5)-(-7y-7)=2 | | 2g-7g=-24 | | 6x+39=14x-66 | | -2(x-4)=12 | | 7x+3y=6x+5y | | -2(-2-4)=12 | | 6=4d-10 | | Y-4=7x(x-3) | | 5+5q=6+4q | | 6(2+-5)+5t=60-1 | | 11-j=2 | | 5+6=9+3 |